2022
DOI: 10.1186/s13063-022-06251-7
|View full text |Cite|
|
Sign up to set email alerts
|

Using a modified nominal group technique to develop complex interventions for a randomised controlled trial in children with symptomatic pes planus

Abstract: Background Children with symptomatic flat feet (pes planus) frequently present for care but there remains uncertainty about how best to manage their condition. There is considerable variation in practice between and within professions. We intend to conduct a three-arm trial to evaluate three frequently used interventions for pes planus (exercise and advice, exercise and advice plus prefabricated orthoses, and exercise and advice plus custom made orthoses). Each of these interventions are comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Short lists of treatment options such as prefabricated and custom-made orthoses, stretching and strengthening exercises, and health promotion and counseling were agreed upon. They concluded that the process of combining data with face-to-face meetings ensured that the interventions are reflected in contemporary practice (Backhouse et al, 2022). Rosero, et al (2021), in the article "Addressing the Data Acquisition Paradigm in the Early Detection of Pediatric Foot Deformities", mention that analysis of plantar pressure through podometry has made it possible to analyze and detect various types of feet in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Short lists of treatment options such as prefabricated and custom-made orthoses, stretching and strengthening exercises, and health promotion and counseling were agreed upon. They concluded that the process of combining data with face-to-face meetings ensured that the interventions are reflected in contemporary practice (Backhouse et al, 2022). Rosero, et al (2021), in the article "Addressing the Data Acquisition Paradigm in the Early Detection of Pediatric Foot Deformities", mention that analysis of plantar pressure through podometry has made it possible to analyze and detect various types of feet in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], we were notified that the third author name was spelled incorrectly as Stewart Morison instead of Stewart Morrison (double “r”).…”
mentioning
confidence: 99%